The Correlation Of Smartphone Addiction And Interpersonal Communication Ability Of Undergraduate Nursing Students - Anggraini, Puspa Dewi; Diding Kelana Setiadi; Rafika Rosyda (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
The existence of smartphones has brought both positive and negative impacts on human life. Unwise use of smartphones can lead to addiction, which affects communication. Establishing good relationships to prevent social alienation in interpersonal communication is important. This study aims to determine the relationship between smartphone addiction and the interpersonal communication skills of undergraduate nursing students and to determine the level of addiction and interpersonal communication skills at each level. The method used is correlational with a cross-sectional approach. The population consists of 464 undergraduate nursing students at the UPI Sumedang Campus with a sample of 215 students, using a stratified random sampling technique. This study uses a questionnaire instrument. Correlation data analysis uses Spearman's rank. The results of the study are that both variables are in the moderate category at each semester level, and the results of the correlation test with a p-value <0.001 (<0.005) have a significant relationship with a correlation coefficient of r -0.224, meaning the strength of the relationship is weak. The negative correlation value means that the higher the smartphone addiction, the lower the interpersonal communication skills. The conclusion of this study is that there is a relationship between smartphone addiction and the interpersonal communication skills of undergraduate nursing students. The level of addiction and interpersonal communication skills of all respondents were in the moderate category. It is recommended for students to use smartphones moderately and more wisely to avoid negative impacts.